Alternative art surfaces : mixed media techniques for painting on more than 35 different surfaces - McElroy, Darlene Olivia. (North Light Books, 2014)
Mixed-media powerhouse duo Darlene Olivia McElroy and Sandra Duran Wilson more than 100 techniques for working on more than 35 unique surfaces, including galvanized tin, mica, rawhide, nylon, unsanded grout, slate, spray foam and more.